Accountants' truth knowledge and ethics in the financial world - Gill, Matthew (Matthew James) (Oxford : Oxford University Press, 2009)
Accounting is the language of business, increasingly standardized across the world through powerful global firms. This ethnographic study shows how decisions and judgements are actually reached, exploring the links between technical knowledge, professional judgement, and ethics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Accountants -- Professional ethics; Accounting -- Moral and ethical aspects; Accounting -- Decision making